Manajemen Integrasi Kurikulum (Integrated Curriculum) Dalam Membentuk Karakter Siswa Unggul di MI Al Mukmin Sragen - Niswatul Khusniyyah; Imam Makruf (Jurnal Pendidikan Indonesia, 2025)
Education in Indonesia faces various challenges, including a lack of attention to character education and the rise of bullying cases. This study uses a qualitative approach with a descriptive method to analyze the application of Islamic education-based management concepts through the integration of the national curriculum and Islamic boarding schools. The results of the study show that curriculum integration can eliminate the boundaries between subjects, so that the material is presented holistically and relevant to students' lives. The integration process is carried out through planning, implementation, and evaluation involving collaboration between teachers and the foundation. With the implementation of an adaptive and inclusive integrative curriculum, it is hoped that it can improve the quality of education and shape student personalities in accordance with religious and cultural values. This journal emphasizes that character education must be the main focus in the education system to produce a generation that is superior and has noble character.